MTFR2 promotes endometrial carcinoma cell proliferation and growth via the miR-132-3p/PI3K/Akt signaling pathway - Niu, Zhijun; Zhang, Yue; Wang, Yishan; Liu, Dongxia; Wang, Junmin; Shi, Tingting; Xu, Xia; Li, Lei (Frontiers in Medicine, 2025)
Objective Understanding the mechanisms underlying endometrial cancer progression is crucial for the development of effective targeted therapies. In this study, we investigated the role of MTFR2 in endometrial cancer cell. Methods The expression of MTFR2 in endometrial cancer was analyzed using The Cancer Genome Atlas (TCGA) dataset and detected in endometrial cancer tissues and cells, respectively. Gain-of-function and loss-of-function approaches were utilized to investigate the impact of MTFR2 on endometrial cancer cell proliferation and tumorigenesis in both in vitro and in vivo settings. Computational tools were employed to predict microRNAs (miRNAs) that potentially regulate MTFR2, and these predictions were experimentally validated. Results The expression of MTFR2 is enhanced in endometrial carcinoma, and it is positively correlated with the poor prognosis of patients. Functional studies show that MTFR2 promoted the proliferation, migration and invasion of endometrial cancer cells. Bioinformatics analysis and luciferase assays identified that MTFR2 is a potential target of miR-132-3p, and transfection with miR-132-3p mimics attenuated the MTFR2-induced activation of the PI3K/Akt pathway. Conclusion Our findings highlight the critical role of MTFR2 in promoting endometrial cancer cell proliferation and growth through the miR-132-3p/PI3K/Akt signaling pathway. Targeting this signaling axis may offer potential therapeutic strategies for endometrial cancer treatment.